Peningkatan Komunikasi Positif Terhadap Narapidana Anak Untuk Mencegah Interaksi Negatif Pada LPKA Kelas II Maros, Makassar - Alimuddin, Alimuddin; Qalby, Moch. Noer Alim; Halizah, Siti Nurul; K, Hairuddin; Muhammad, Muhammad (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
This study aims to improve positive communication among juvenile inmates at LPKA Class II Maros, Makassar, in order to prevent negative interactions that can hinder the rehabilitation process. The main problem faced is the high incidence of negative interactions such as fighting and bullying among juvenile inmates, which adversely affects the coaching atmosphere and their psychological development. This study used a qualitative approach with observation, interview, and focus group discussion methods to understand the dynamics of interactions that occur. The intervention program implemented included communication skills training, counseling sessions, and group activities that support cooperation and mutual understanding. The results showed that there were significant improvements in children's communication skills, such as the ability to speak well, listen actively, and resolve conflicts without violence. In addition, there was a significant reduction in the incidence of negative interactions, creating an environment more conducive to rehabilitation. LPKA officers also reported improvements in their communication skills, which contributed to a better working atmosphere and less stress. This study concludes that positive communication programs are effective in reducing negative interactions and recommends the implementation of similar programs in other child development institutions. The contribution of this research is that it provides an intervention model that can be applied to support the rehabilitation of juvenile prisoners in a more holistic and sustainable manner.